INFLUENCIA DE LA CONCENTRACION DEL HIDROXIDO DE CALCIO EN LA OBTENCION DEL SULFATO DE NICOTINE - LEON ESPERON, S; HOPE, HENRY PHILIP (Instituto Nacional de Cardiología, CD MEXICO, DF, MEX, 1948)
The development of the Physalis fruit induced by the action of chemical substances, activators of growth, produces in the fruits a greater conc of sugars and a lowering of the total ascorbic acid The difference in the ascorbic acid (reduced form) betwee
AN ESC NAC CIENC BIOL
Keywords: INFLUENCIA, CONCENTRACION, HIDROXIDO DE CALCIO, OBTENCION, SULFATO DE NICOTINE; CIENCIAS DE LA VIDA; BIOLOGIA CELULAR; CULTIVO CELULAR